2022
DOI: 10.3390/life12070995
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Gene Transfer to Gene Duplication Ratios Identify Different Roots in the Bacterial Phylogeny Using a Tree Reconciliation Method

Abstract: The rooting of phylogenetic trees permits important inferences about ancestral states and the polarity of evolutionary events. Recently, methods that reconcile discordance between gene-trees and species-trees—tree reconciliation methods—are becoming increasingly popular for rooting species trees. Rooting via reconciliation requires values for a particular parameter, the gene transfer to gene duplication ratio (T:D), which in current practice is estimated on the fly from discordances observed in the trees. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…Based on this understanding, we summarise what published analyses have concluded about variation in the processes of molecular evolution across the tree of life. We also clarify a number of potential misconceptions about these methods and their results in the recent critiques (Tria & Martin 2021; Bremer et al 2022), and show that reconciliation-based inferences about frequencies of duplication, transfer and loss are in good agreement with previous results using other methods. Finally, we provide a practical guide for researchers who wish to use reconciliation tools to perform phylogenomic and comparative genomic analyses, review current limitations and suggest future directions for addressing them.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Based on this understanding, we summarise what published analyses have concluded about variation in the processes of molecular evolution across the tree of life. We also clarify a number of potential misconceptions about these methods and their results in the recent critiques (Tria & Martin 2021; Bremer et al 2022), and show that reconciliation-based inferences about frequencies of duplication, transfer and loss are in good agreement with previous results using other methods. Finally, we provide a practical guide for researchers who wish to use reconciliation tools to perform phylogenomic and comparative genomic analyses, review current limitations and suggest future directions for addressing them.…”
Section: Introductionsupporting
confidence: 69%
“…In their recent critique of ALE, (Bremer et al 2022) suggested that estimated rates of duplication and transfer were biologically unrealistic for two datasets from different domains of life because they failed to capture the expected difference in the dynamics of genome evolution between Bacteria (Coleman et al 2021) and eukaryotes (Bremer et al 2022). To evaluate these claims, we summarised the ALE output from the two datasets (Figure 3).…”
Section: Do Prior Assumptions Bias the Estimation Of Model Parameters...mentioning
confidence: 99%
See 3 more Smart Citations